Estimating the Relative Stiffness between a Hepatic Lesion and the Liver Parenchyma through Biomechanical Simulations of the Breathing Process. (25th October 2018) - Martínez-Sanchis, S.; Rupérez, M. J.; Nadal, E.; Pareja, E.; Brugger, S.; Borzacchiello, D.; López-Andújar, R.; Monserrat, C.
Abstract : In this paper, a method to in vivo estimate the relative stiffness between a hepatic lesion and the liver parenchyma is presented. This method is based on the finite element simulation of the deformation that the liver undergoes during the breathing process. Boundary conditions are obtained through a registration algorithm known as Coherent Point Drift (CPD), which compares the liver form in two phases of the breathing process. Finally, the relative stiffness of the tumour with respect to the liver parenchyma is calculated by means of a Genetic Algorithm, which does a blind search of this parameter. The relative stiffness together with the clinical information of the patient can be used to establish the type of hepatic lesion. The developed methodology was first applied to a test case, i.e., to a control case where the parameters were known, in order to verify its validity. After that, the method was applied to two real cases and low errors were obtained.